2019
DOI: 10.1111/aje.12628
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the spatial patterns of vertebrate roadkill in South Africa: The Greater Mapungubwe Transfrontier Conservation Area as a case study

Abstract: Few studies have investigated the factors that influence roadkill occurrence in developing countries. In 2013, we monitored a 100‐km section of the road (comprising the R572 and R521 regional highways and the D2662) that pass through the Greater Mapungubwe Transfrontier Conservation Area in South Africa, to assess the possible factors influencing roadkill. Over a period of 120 days, and across the three ecological seasons, we recorded 981 roadkills (rate = 0.08 roadkill/km/day) from four vertebrate taxonomic g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
0
6
1
Order By: Relevance
“…In terms of numbers, small to medium-sized mammals were the most abundant roadkill (53%), followed by birds (32%), reptiles (10%), and lastly large mammals (5%). These findings contrast those from Tarangire-Manyara ecosystem and Mapungubwe Transfrontier conservation area in South Africa, where birds were the most common roadkill at 50% and mammals (large and small to medium-sized combined) came second at 27–30% ( Kioko et al., 2015 ; Collinson et al., 2019 ). The deviation in taxon composition represented in roadkill across studies may also be influenced by data collection protocols such as the timing of surveillance, and speed of the drive during monitoring.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…In terms of numbers, small to medium-sized mammals were the most abundant roadkill (53%), followed by birds (32%), reptiles (10%), and lastly large mammals (5%). These findings contrast those from Tarangire-Manyara ecosystem and Mapungubwe Transfrontier conservation area in South Africa, where birds were the most common roadkill at 50% and mammals (large and small to medium-sized combined) came second at 27–30% ( Kioko et al., 2015 ; Collinson et al., 2019 ). The deviation in taxon composition represented in roadkill across studies may also be influenced by data collection protocols such as the timing of surveillance, and speed of the drive during monitoring.…”
Section: Discussioncontrasting
confidence: 82%
“…These projects will crisscross the continent passing through remote regions and key ecosystems that sustain high levels of biodiversity. There are limited studies on the ecological impacts of roads in the African tropics (But see: Caro et al., 2014 ; Kioko et al., 2015 ; Nyirenda et al., 2017 ; Collinson et al., 2019 ), where road infrastructure development is projected to grow rapidly into pristine environments and protected areas ( Laurance et al., 2015 ; Alamgir et al., 2017 ). Most road ecology studies have focused on understanding impacts of roads on wildlife in developed countries and temperate biomes ( Dean et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Predictive modelling approaches provide strong support in the investigation of the environmental factors affecting roadkill risk, thus enabling researchers to relate roadkill events to road-related characteristics (e.g., Malo et al 2004;Green-Barber and Old 2019;Collinson et al 2019), as well as to predict areas where roadkill risk is higher, integrating data on habitat suitability and connectivity (Girardet et al 2015;Fabrizio et al 2019a, b;Russo et al 2020). Such studies provide important information that can be used by road managers to develop adequate road designs through the implementation of mitigation measures (Malo et al 2004;Plante et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have identified the factors that have the strongest effect on WVCs (Bencin et al 2019 ; Williams et al 2019 ). Some factors for roadkill occurrence are known; land use (Fillus et al 2020), road characteristics and fencing (Collinson et al 2019 ), ecology of species (Williams et al 2019 ) and population size (Grilio et al 2020). Traffic volume and vehicle speed are the two most important factors affecting the location and numbers of roadkill (Farmer and Brooks 2012 ; Lin 2016 ; Zhang et al 2018 ; Filius et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%